Improved PSO with Disturbance Term for Solving ORPD Problem in Power Systems - Mezaache, Mohamed; Benaouda, Omar Fethi; Sekhane, Hocine; Chaouch, Saad; Babes, Badreddine (Advances in electrical and electronic engineering, 2022)
The essential purpose of an energy system is to provide electricity to its loads effectively and economically, as well as safely and reliably. Therefore, the solutions to the problems of Optimal Power Flow (OPF) and Optimal Reactive Power Dispatch (ORPD) to enable the efficient employment of various energy distributions should be found. Our work focuses on the ORPD issue; it can be formulated as a non-linear constraint and with single or multiple objectives optimization problems. Minimizing total losses is one of the main objective functions to solve the ORPD problem. This paper presents the use of an improved particle swarm optimization -with a disturbance term- (called PSO-DT) algorithm, to find the solution of ORPD in the standard IEEE 30-bus power system for reducing electrical power transmission losses. The obtained results demonstrate that the proposed method is more efficient and has a more extraordinary ability to get better solutions compared to the basic PSO method.